RTL-SDR Audio Signal Optimization Using Noise Reduction and Fast Fourier Transforms - Aviv Yuniar Rahman (International Conference on Industrial Revolution for Polytechnic Education, 2019)
In a radio device such as RTL SDR (RealtekSoftware Defined Radio), we often encounter noise orinterference with data received by RTL SDR. Noise is anunwanted signal that is acoustic, electrical and electronic.Noise will interfere with the process of receiving and sendingdata so that the data received is not in accordance with thedata sent. Noise reduction is the process of removing unwantedsounds from the signal. In this paper, we address the problemof reducing noise signal using Gaussian Filter and a SavitzkyGolay smoothing filter. Then, the output signal analyzed byusing the Fast Fourier Transform (FFT) method. With theFFT method, the display of the FFT frequency, sound signalwaveform and the time value row in the .wav file are obtained.The recordings of the RTL SDR will be processed using thenoise reduction method to eliminate noise in the data, then usethe FFT method to display the FFT frequency, sound signalwaves and rows of time values in the data. The optimal resultsobtained in the final iteration are 10th or n-points 1024iterations with a minimum value of 0.0012 and a maximum of0.7219.